2003
DOI: 10.1076/opep.10.3.177.15084
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of cataract patients: cross-cultural comparisons of utility and psychometric measures

Abstract: Subjects in Korea and the United States were significantly different in quality of life, functional status and clinical outcomes. Subjects in the United States had more favorable health outcomes than those in Korea. These differences may be caused by multiple factors, including country-specific differences in economic status, health care system, cultural value system, and health policy. Cross-cultural differences should be considered when making international comparisons of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Another difference in characteristics was that older and higher educated patients participated in the study in United States than in Korea. However, Lee et al [11] concluded that even though there was significant difference in estimated quality of life scores between two countries, these differences were not found to result from the difference in patient characteristics. This result was supported by this study which determined the relationships were persistent even after controlling socio-demographic variables.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another difference in characteristics was that older and higher educated patients participated in the study in United States than in Korea. However, Lee et al [11] concluded that even though there was significant difference in estimated quality of life scores between two countries, these differences were not found to result from the difference in patient characteristics. This result was supported by this study which determined the relationships were persistent even after controlling socio-demographic variables.…”
Section: Discussionmentioning
confidence: 94%
“…After initially agreeing to participate, four Korean and six United Sates patients refused to participate in the interview due to time limitation or other personal reasons. Details of the sampling method are described elsewhere [10,11]. Since the influence of surgery on patient attitude might vary, in an attempt to mitigate the effect of confounding data were collected at the time of preoperative ultrasound testing.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Nevertheless, the high utility values in our population may be attributed to the disease severity profile or systemic comorbidities. 5,9,16,17 Mean logMAR BEVA and WEVA in this study were 0.20 and 0.65, respectively, indicating generally less severe disease (Tables 5 and 6). Direct comparison of utilities should be approached cautiously, as scores are affected when top, bottom, or both anchors of utility instruments are changed.…”
Section: Eyementioning
confidence: 97%
“…[7][8][9] To the best of our knowledge, no studies have examined these instruments for AMD in Asian populations. Assessment of population-specific utility values for AMD is of economic relevance in many Asian health-care systems, owing to rising health-care costs and resource allocation challenges, especially with the high prevalence of heart disease and cancers.…”
Section: Introductionmentioning
confidence: 99%
“…So what makes governments decide? The answer is simple: the health burden associated with cataracts has been well characterized (14)(15)(16), whereas the health burden of breast hypertrophy has only recently been measured (17).…”
mentioning
confidence: 99%